Recyclable Waste Management System for Tzu Chi Recycling Activities - Liaw, Jing Yin; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2022)
A recycling collection center is an organization that collects recycledmaterials for the purpose of resale or conversion to other products. these centersare usually run by companies or individuals. However, there are several issuesencountered in managing activities at recycling center including manual entry fordata storage, manpower task management, and lack of a systematic system tosupport recycling activities. To support recycling activities at the case studylocation, Tzu Chi, a system was developed for administrators, volunteers, anddrivers at this recycling center. The system allows users to keep records of recycledwaste collected in a database. Administrators can retrieve records to generatereports, create payment invoices, and control task management. The system wasdeveloped with a prototype-based methodology and system analysis was conductedin an object -oriented approach. This system was developed with MAMP, PHP, andSublime. Through this system, users at the recycling center can manage theirrecycling activities more efficiently especially the management of their operationaldata. The system is also expected to keep all records of recycling waste, theactivities, and other related transaction record in the database.